Concern over MQE standards - The Sun, Pauline Wong (2012)
PETALING JAYA: The medical fraternity has raised concerns about the impact on exam standards if all 33 local public and private medical varsities-are allowed to-conduct the Medical Qualifying Exam (MQE).